2010
DOI: 10.1890/09-1277.1
|View full text |Cite
|
Sign up to set email alerts
|

Rapid response of a grassland ecosystem to an experimental manipulation of a keystone rodent and domestic livestock

Abstract: Megaherbivores and small burrowing mammals commonly coexist and play important functional roles in grassland ecosystems worldwide. The interactive effects of these two functional groups of herbivores in shaping the structure and function of grassland ecosystems are poorly understood. In North America's central grasslands, domestic cattle (Bos taurus) have supplanted bison (Bison bison), and now coexist with prairie dogs (Cynomys spp.), a keystone burrowing rodent. Understanding the ecological relationships bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
92
1
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(97 citation statements)
references
References 54 publications
(118 reference statements)
2
92
1
2
Order By: Relevance
“…Moser and Witmer (2000) found that ungulate grazing in a steppe area also reduced shrub abundance and small mammal diversity, but plant and bird diversity were unaffected. Davidson et al (2010) conducted a 3-year, smallscale replicated experiment, manipulating two grazing species, cattle and prairie dogs Cynomys ludovicianus, in a grassland in Mexico and found variable effects of cattle on rodents, and synergistic effects of cattle and prairie dogs on vegetation structure and invertebrates. In Norway, a large-scale replicated experiment was conducted that manipulated sheep grazing and found variable short-term effects on plants (Austrheim et al 2008), invertebrates (Mysterud et al 2010), birds (Loe et al 2007) and small mammals (Steen et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Moser and Witmer (2000) found that ungulate grazing in a steppe area also reduced shrub abundance and small mammal diversity, but plant and bird diversity were unaffected. Davidson et al (2010) conducted a 3-year, smallscale replicated experiment, manipulating two grazing species, cattle and prairie dogs Cynomys ludovicianus, in a grassland in Mexico and found variable effects of cattle on rodents, and synergistic effects of cattle and prairie dogs on vegetation structure and invertebrates. In Norway, a large-scale replicated experiment was conducted that manipulated sheep grazing and found variable short-term effects on plants (Austrheim et al 2008), invertebrates (Mysterud et al 2010), birds (Loe et al 2007) and small mammals (Steen et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Grasslands are fundamentally shaped by two key functional groups that have co-evolved for thousands of years, namely, large migratory mammalian herbivores and small to medium-sized burrowing herbivorous mammals [7,8]. Both functional groups of herbivores play keystone and/or ecosystem engineering roles and have complementary and interactive effects on grassland ecosystem structure and function [912].…”
Section: Introductionmentioning
confidence: 99%
“…Abundances of small mammals are influenced by changes in habitat structure, including removal of woody debris [15,16] and cover of grasses [17,18], so biofuels production may affect population dynamics and habitat relationships of rodents. Population abundance can be influenced by changes in habitat structure and quality, and a range of demographic parameters determines population abundance.…”
Section: Introductionmentioning
confidence: 99%